γ‐Agregation operators and some aspects of generalized aggregation problem - Lebedinska, Julija (Mathematical Modelling and Analysis, 2010)
We explore questions related to the aggregation operators and aggregation of fuzzy sets. No preliminary knowledge of the aggregation operators theory and of the fuzzy sets theory are required, because all necessary information is given in Section 2. Later we introduce a new class of γ‐aggregation operators, which “ignore” arguments less than γ. Due to this property γ‐aggregation operators simplify the aggregation process and extend the area of possible applications. The second part of the paper is devoted to the generalized aggregation problem. We use the definition of generalized aggregation operator, introduced by A. Takaci in [7], and study the pointwise extension of a γ‐agop. First published online: 09 Jun 2011